SUSCEPTIBILITY STATUS OF XENOPSYLLA CHEOPIS AND XENOPSYLLA ASTIA TO MALATHION - KUMAR, ARVIND; SINGH, P.P.; KUMAR, KAUSHAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The toxicity of malathion was tested on two species of rat fleas namely Xenopsylla cheopis and X. astia in Distt Baghpat of Western Uttar Pradesh. The fleas were exposed for one hour. The mortality of 82.15% was recorded in X. Cheopis and 85.71% in X. astia. Males of both the species showed more sensitivity to insecticide than females.